Built heritage and flash floods: hiking trails and tourism on Madeira Island. Issue 1 (2nd January 2016) - Fernandes, Filipa
Abstract : High-magnitude, low-frequency rain events (heavy rains) have increased on the island of Madeira in recent years. The levadas, a built heritage of water canals, and one of the biggest tourist attractions on the island due to their role as hiking trails, have been repeatedly damaged as a result of heavy rains causing problems that affect stakeholders, regional governments and local communities. Using ethnographic methods this study analyses the relations between tourism, actors and climate change and especially the vulnerability of tourism spaces (hiking trails) as a result of increased risk and (in)security.